Functional recovery in senior adults undergoing surgery for colorectal cancer: Assessment tools and strategies to preserve functional status. Issue 3 (March 2020) - Ghignone, F.; Hernandez, P.; Mahmoud, N.N.; Ugolini, G.
Abstract: Colorectal cancer is a widely-recognized aging-associated disease. Recent advances in the care of senior colorectal cancer patients has led to similar cancer-related life expectancy for older patients when compared to their younger counterparts. Recent data suggests that onco-geriatric patients place as much value on maintenance of functional independence and quality of life after treatment as they do on the potential improvements in survival that a treatment might offer. As a result, there has been significant interest in the geriatric literature surrounding the concept of "functional recovery, " a multidimensional outcome metric that takes into account several domains, including physical, physiologic, psychological, social, and economic wellbeing. This review introduces the concept of functional recovery and highlights a number of predictors of post-treatment functional trajectory, including several office-based tools that clinicians can use to help guide informed decision making surrounding potential treatment options. This review also highlights a number of validated metrics that can be used to assess a patient's progress in functional recovery after surgery. While the timeline of each individual's functional recovery may vary, most data suggests that if patients are to return to their pre-operative functional status, this could occur up to 6 months post-surgery. For those patients identified to be at risk for post-operative functional decline this review also delineates strategies for prehabilitation and rehabilitation that may improve functional outcomes.